Gated mesoporous nanomaterial, preparation method thereof and kit

By using gated mesoporous nanomaterials based on dendrimer-bound aptamers in the rapid detection test strips, the problems of sealing instability and slow signal release rate are solved, high sensitivity detection is achieved, and the separate detection of macromolecules and small molecule targets is supported.

CN119510746AActive Publication Date: 2025-02-25ZJU HANGZHOU GLOBAL SCI & TECH INNOVATION CENT
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311733233.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-15
Publication Date
2025-02-25
Estimated Expiration
2043-12-15

AI Technical Summary

Technical Problem

Aptamer-gated mesoporous materials have problems such as unstable sealing, slow signal release rate and low detection sensitivity in rapid detection test strips.

Method used

Using gated mesoporous nanomaterials based on dendrimer binding aptamers, stable sealing and rapid signal release are achieved by loading signal molecules into mesoporous nanoparticles and coupling them with target-specific aptamers.

Benefits of technology

It realizes good sealing stability and fast signal release rate of gated mesoporous nanomaterials, improves the detection sensitivity of fast detection test strips, and can detect large and small molecular targets respectively under the same detection mechanism.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119510746A_ABST
    Figure CN119510746A_ABST
Patent Text Reader

Abstract

The invention discloses a gated mesoporous nanomaterial, a preparation method thereof and a kit, and belongs to the technical field of detection. According to the preparation method disclosed by the invention, the gated mesoporous nano material has good sealing stability and high signal release rate. Meanwhile, based on an application method of the nano material in a rapid detection kit, a signal amplification function of rapid detection test paper is realized, the detection sensitivity of the test paper is improved, and macromolecular and micromolecular targets can be respectively detected under the same detection mechanism.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of detection technology, and specifically relates to a gated mesoporous nanomaterial and a preparation method and a kit thereof. Background Art

[0002] Aptamer-gated mesoporous materials are widely used in the field of target detection. Mesoporous materials have a large internal volume, and their properties allow many signal molecules (such as fluorescent dyes, etc.) to be loaded inside the mesoporous materials. At the same time, mesoporous materials have controllable pore sizes, which can be sealed by aptamers to block the small molecule materials loaded inside; then, the sealing materials will bind to external targets, resulting in structural changes in the sealing materials to open the blocked pores and release the signal molecules loaded inside the mesoporous materials, which is the "gating" effect. The advantage of using aptamer-gated mesoporous materials is that a small amount of the substance to be tested can stimulate the release of a large number of signal molecules, ultimately forming an amplification of the detection signal and improving the detection sensitivity.

[0003] The quality of "gating" directly depends on the method of sealing the material. Traditional sealing methods are generally divided into three types. The first method is the electrostatic adsorption method, which uses the electrostatic attraction between the mesoporous material and the sealing material to cover the sealing material on the surface of the mesoporous material to block the pore size. This method is considered to be the simplest and most universal method, but its stability is poor because the electrostatic attraction can be easily destroyed by changes in external conditions such as ion concentration, temperature, and pH, resulting in leakage of internal signal molecules. The second method is the "plugging method", in which the sealing aptamer is designed as a "plug" to block the pore size of the mesoporous material. Specifically: the mesoporous material is covalently coupled to the aptamer, and the aptamer is designed to form a hairpin structure, which is like a "plug" to block the pores to prevent the internal material from leaking. Subsequently, once coupled with the target, its secondary structure changes, causing the pores to open and release the internal signal molecules. However, this design usually has unstable capping, resulting in leakage of internal signal molecules, which can cause false positives during target detection. The third method is the "bridging" method, which uses a group of sealing aptamers to form a "bridge" to block the pore size of the mesoporous material. Specifically, the mesoporous material is covalently coupled to the arm-shaped ssDNA, and then the arm-shaped ssDNA combines with the aptamer through complementary base pairing to form a "bridge" to seal the mesopore. Once the aptamer is coupled to the target, it can cause the aptamer to separate from the arm-shaped ssDNA, causing the pore to open and release the internal signal molecules. However, since the single-stranded size of the aptamer is smaller than the mesoporous pore (1nmvs.3nm), there will also be leakage of internal signal molecules. If the "bridge" is formed in the form of a double-stranded DNA, the "bridge" bonding force is too strong, and the aptamer is not easily separated from the arm-shaped ssDNA, resulting in failure to release the signal molecule. In addition, both the "plugging method" and the "bridging method" couple the aptamer or arm-shaped ssDNA to the surface of the mesoporous material, which will affect the release of internal signal molecules. When the mesoporous pores are relatively small (for example, ~3nm), the signal release will be too slow, which is not conducive to the application in the field of rapid detection. If large-sized mesoporous pores are used, this will cause loose sealing and leakage of signal molecules.

[0004] Based on the above reasons, aptamer-gated mesoporous materials have not been used in the development of rapid test strips. This is because rapid test strips require ligand-gated mesoporous materials to have good sealing stability to ensure that signal molecules do not leak, as well as a fast signal release rate.

[0005] Rapid test strips are a chromatography-based on-site rapid detection and analysis method. Due to its significant cost-effectiveness, it has been widely used in many fields, such as diagnosis and food safety. Most test strips use a sandwich test format. In a positive test, the analyte in the sample binds to the gold nanoparticle-labeled primary antibody and moves along the paper strip by capillary action, and is captured by the target secondary antibody on the test line (T line), thereby forming a visible signal on the T line (i.e., the aggregation of gold nanoparticles). To ensure the accuracy of the test results, a control line (C line) is usually set downstream of the T line. It is usually assembled from anti-primary antibody antibodies. Regardless of whether the test result is positive or negative, the C line should show a signal to ensure that the test is valid.

[0006] Although many test strips have been successfully commercialized, such as early pregnancy and ovulation test strips, their detection sensitivity is relatively low. This problem stems from the fact that when the concentration of the target analyte is low, the concentration of the target-gold-labeled antibody that can generate a signal is too low, so too little aggregation on the T line cannot generate a significant signal. At the same time, the test strips also lack the corresponding signal enhancement mechanism. Therefore, rapid test strips are usually only used when the concentration of the target analyte is high, such as early pregnancy tests during pregnancy, where the concentration of human chorionic gonadotropin increases significantly. In order to improve the detection sensitivity of the paper strip detection platform, people have tried to use high-efficiency fluorescent quantum dots to replace gold nanoparticles as signal agents to enhance the signal, but the signal amplification function is limited and there is still a lot of room for improvement.

[0007] In addition, when using rapid test strips to detect small molecules, the sandwich method is not suitable for detection because the small molecule target has few binding sites, so the competition method is mainly used. The principle of the competition method is to achieve the test effect through competition with colloidal gold-labeled antibodies. This method uses a small amount of antibody and colloidal gold to couple and coat the sample binding pad, and coat the antigen at the T line. During the detection process, when the detected antigen exists in the sample, the antigen in the sample first binds to the gold-labeled antibody. Because the content of the gold-labeled antibody is small, the antigen at the T line can no longer bind to the gold-labeled antibody, so no color is developed. When the sample is negative, the antigen at the T line can bind to the gold-labeled antibody and develop color. However, the sensitivity of the test strip detection based on the competition method is not as high as that of the test strip detection based on the sandwich method. At the same time, when the concentration of the antigen is very low, if the antigen cannot completely occupy the antibody at the binding pad, it may produce a false negative result. Summary of the invention

[0008] In order to solve the problems of unstable sealing, slow signal release rate and low detection sensitivity of the above-mentioned aptamer-gated mesoporous materials, the present invention provides a gated mesoporous nanomaterial based on dendritic macromolecules combined with aptamers and a preparation method thereof, so that the gated mesoporous nanomaterial has good sealing stability and fast signal release rate. At the same time, a method for applying this nanomaterial to a rapid detection kit is also provided to realize the signal amplification function of the rapid detection test strip, improve the detection sensitivity of the test strip, and detect macromolecules and small molecules respectively under the same detection mechanism.

[0009] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0010] A method for preparing a gated mesoporous nanomaterial, wherein the gated mesoporous nanomaterial can be used to prepare a test strip, comprises the following steps:

[0011] (1) Loading signal molecules into mesoporous nanoparticles to obtain signal molecule-loaded mesoporous nanoparticles OSM@MSNs.

[0012] (2) coupling the target-specific aptamer to the OSM@MSNs obtained in step (1) to obtain the OSM@MSNs-aptamer coupled to the surface of the mesoporous nanoparticles carrying the signal molecule,

[0013] (3) coupling ssDNA with the nth generation carboxyl polyamide-amine dendrimer to obtain ssDNA-Gn, wherein n≥3.5,

[0014] The ssDNA is used to bind to the aptamer in step (2) and is competitively dissociated in the presence of the detection target.

[0015] (4) Assembling the ssDNA-Gn obtained in step (3) with the OSM@MSNs-aptamer obtained in step (2), and allowing the nth generation carboxyl polyamide-amine dendrimer to seal the mesoporous nanoparticles through the binding between the ssDNA and the aptamer.

[0016] In the present embodiment, the 3.5 generation carboxylic polyamide-amine dendrimer is used as an example, because the molecular size is just larger than the mesopore size. In terms of experimental principle, as long as the macromolecule is larger than the mesopore size, it will be fine. For example, carboxylic polyamide-amine dendrimers of the 4th, 4.5th, 5th, and 5.5th generations are all fine.

[0017] Preferably, the signal molecule is at least one of rhodamine B, fluorescein isothiocyanate, Cy3, Cy5 and fluorescein. The mesoporous nanoparticles are mesoporous silica nanoparticles, mesoporous titanium dioxide nanoparticles, metal organic frameworks, mesoporous alumina, mesoporous magnetic beads, mesoporous ferrosoferric oxide or mesoporous copper sulfide nanoparticles.

[0018] Specifically, in step (2), when the target-specific aptamer is coupled to the OSM@MSNs obtained in step (1), the N=C=O group is introduced by functionalizing the surface of the OSM@MSNs obtained in step (1), and the end group of the aptamer is modified with an amino group, and the coupling is carried out by reaction between the N=C=O group and the amino group;

[0019] Alternatively, the surface of OSM@MSNs obtained in step (1) is functionalized to introduce amino groups, the terminal group of the aptamer is modified with -SH groups, and the aptamer is coupled with Na-maleimidoacetyl-oxysuccinimide ester.

[0020] Alternatively, -SH groups are introduced by functionalizing the surface of OSM@MSNs obtained in step (1), the end groups of the aptamer are modified with amino groups, and the aptamer is coupled with Na-maleimidoacetyl-oxysuccinimide ester;

[0021] Alternatively, the surface of OSM@MSNs obtained in step (1) is functionalized to introduce amino groups, the end group of the aptamer is modified with amino groups, and the aptamer with amino groups is coupled with glutaraldehyde or (bis(sulfosuccinimidyl) suberate);

[0022] In step (3), when ssDNA is coupled with the nth generation carboxyl polyamide-amine dendrimer to obtain ssDNA-Gn, the two undergo a coupling reaction mediated by EDC / NHS.

[0023] Preferably, the size of the mesoporous nanoparticles is 3 to 5 nm.

[0024] More preferably, the size of the mesoporous nanoparticles is 4 nm.

[0025] Traditional aptamer gated mesoporous nanomaterials usually use MCM-41 (with a pore size of about 3nm) as a carrier to meet the needs of different aptamer structures (single-chain is about 1nm, double-chain is about 2nm) for blocking mesopores, but the blocking effect is not ideal because the size of the blocking structure is much smaller than the size of the mesopores (as described in the background). The embodiment of the present invention uses an aptamer combined with G3.5 as a sealing material. The molecular size of G3.5 is about 4.5nm, which is larger than the mesopore size (4nm) used in the present invention. Therefore, the sealing effect is stable and there will be no problem of signal molecule leakage.

[0026] The gated mesoporous nanomaterial MCM-41 of the traditional aptamer has a pore size of about 3nm and a slow release rate of signal molecules, so it can only be used in scenarios where the detection rate requirements are not high. The mesopore size used in the present invention is 4nm, and the signal molecules are released faster; therefore, it can be used in rapid detection fields such as rapid detection strips. Other similar mesoporous materials have a mesopore size of less than 3nm and can achieve similar effects, but the final release rate is not good.

[0027] The invention also provides a gated mesoporous nanomaterial prepared by the preparation method.

[0028] The present invention also provides the use of the gated mesoporous nanomaterial in preparing a detection kit, wherein the kit comprises a detection test strip, the detection test strip comprises a conjugation pad, a detection line T line, and a quality control line C line, and the gated mesoporous nanomaterial is embedded in the conjugation pad.

[0029] The present invention also provides a rapid test paper kit based on the gated mesoporous nanomaterial, the kit comprising a test paper strip, the test paper strip comprising a conjugate pad, a detection line T line, and a quality control line C line, the conjugate pad being embedded with the gated mesoporous nanomaterial.

[0030] Preferably, the conjugate pad is further embedded with fluorescein, the detection line T is embedded with an antibody against the signal molecule, and the quality control line C is embedded with an anti-fluorescein antibody against the fluorescein.

[0031] In order to improve the detection sensitivity of the test strip, macromolecules and small molecule targets can be detected separately under the same detection mechanism. We invented a test strip detection method based on gated mesoporous nanomaterials with dendritic macromolecules combined with aptamers. This method provides a signal amplification mechanism on the test strip detection platform and enhances the detection sensitivity. At the same time, this detection mechanism can meet the detection of macromolecules and small molecule targets separately.

[0032] Its structure and detection mechanism are as follows Figure 2 As shown, the porous silica nanoparticles gated by aptamer / G3.5 are used to load rhodamine B (used as a fluorescent signal molecule on the T line) and are embedded in the conjugate pad; at the same time, fluorescein is also embedded in the conjugate pad, which is used as a fluorescent signal molecule on the C line. In addition, the T line and C line of the paper strip are respectively embedded with anti-rhodamine B and anti-fluorescein antibodies, which are used to specifically capture these two fluorescent signal molecules.

[0033] When the sample is positive, the target will bind to the aptamer on the surface of the porous silica nanoparticles, destroying the bonding force between the aptamer and ssDNA, dissociating the G3.5 molecules used for sealing, and releasing a large number of rhodamine B signal molecules. The released rhodamine B signal molecules will be captured by antibodies at the T line along the direction of water flow, thus showing red, while the fluorescent signal molecules will be captured at the C line, showing green as a quality control.

[0034] When the sample is negative, the Rhodamine B signal molecule will not be released, so the T line will not show color, and the C line will still appear green.

[0035] The specific production plan of the test strips is as follows:

[0036] (1) Sample pad preparation

[0037] The sample pad material is glass fiber, which is pre-soaked in blocking buffer for 12 hours and then dried for use. The blocking buffer composition is 1X PBS (pH 7.4), 5% bovine serum albumin, 5% sucrose, 0.01% Tween-20, 0.02% Triton X-100, and 0.01% proclin 300.

[0038] (2) Bonding pad production

[0039] The main material of the conjugate pad is a polyester membrane, which is pre-soaked in a blocking buffer for 12 hours, dried, sprayed with 1 mg / mL OSM@MSNs-aptamer / G3.5 (where the signal molecule is rhodamine B) and 10 μg / mL fluorescein, and then dried for use. The blocking buffer composition is 1X PBS (pH 7.4), 5% bovine serum albumin, 5% sucrose, 0.01% Tween-20, 0.02% Triton X-100, and 0.01% proclin 300.

[0040] (3) T-line and C-line

[0041] 1 mg / mL anti-rhodamine B and anti-fluorescein antibodies were sprayed on the T and C lines of the nitrocellulose membrane, respectively, with a spacing of 4 mm between the T and C lines, and then dried at 37°C.

[0042] (4) Assembly

[0043] The test strips consist of a sample pad, conjugate pad, nitrocellulose membrane and adsorbent pad overlap assembly assembled on a PVC card. First, the conjugate pad is slightly covered on the nitrocellulose membrane, and then the sample pad is placed to overlap the conjugate pad. The conjugate pad and sample pad are placed at the end of the nitrocellulose membrane, and on the other side of the membrane, the adsorbent pad overlaps the nitrocellulose membrane. All overlap areas are 2mm in length. The final assembled card is cut into 3mm long strips and then stored in a desiccator before use.

[0044] Beneficial effects of the present invention:

[0045] 1. The gated mesoporous nanomaterial of the present invention has stable sealing, no leakage of signal molecules and fast release speed.

[0046] 2. The gated mesoporous nanomaterial of the present invention has a strong ability to prevent interference from nonspecific targets in the matrix. G3.5 has excellent surface antifouling properties. When used as a sealing material, it can prevent interference from nonspecific targets in the matrix to the surface aptamer, reducing the false positive phenomenon caused by nonspecific adsorption or the phenomenon of increased background noise.

[0047] 3. The present invention provides a signal amplification scheme for the test strip, thereby improving the detection sensitivity. The traditional signal amplification scheme is to use nanoparticles with stronger signals (such as quantum dots, fluorescent latex microspheres, etc.) instead of gold nanoparticles, which is essentially an improvement in signal intensity. The present invention uses a small amount of target to excite a large number of signal molecules, thereby amplifying the detection signal in terms of signal quantity.

[0048] 4. The present invention can detect macromolecules and small molecule targets separately under the same detection mechanism. Unlike traditional colloidal gold test strips, the detection of large target substances requires the use of a sandwich method, and the detection of small molecule substances requires the use of a competitive method. The present invention binds to the target through the aptamer, opens the G3.5 seal, and releases the signal molecule; therefore, the present invention provides a universal test strip detection scheme, which can detect macromolecules and small molecule targets separately without changing the detection mechanism. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 Flow chart of the method for preparing gated mesoporous nanomaterials based on dendrimer-binding aptamers.

[0050] Figure 2 Schematic diagram of the paper strip structure and the detection principle.

[0051] Figure 3 The fluorescence intensity diagram is used to characterize the coupling of aptamer and mesoporous nanomaterials by using fluorescently labeled aptamer.

[0052] Figure 4 The fluorescence intensity graph is a graph showing the coupling of ssDNA and G3.5 by using fluorescently labeled ssDNA.

[0053] Figure 5 The particle size changes during the synthesis steps.

[0054] Figure 6 This is a test diagram of gating performance and signal molecule release rate.

[0055] Figure 7 The effect of milk matrix on seal stability.

[0056] Figure 8 Rapid test strips based on gated mesoporous nanomaterials with dendrimer-binding aptamers were used to test ochratoxin A in real milk samples.

[0057] Fig. 9 Silica nanoparticles produced by the "plugging method".

[0058] Fig.10 Silica nanoparticles produced by the "bridge method". DETAILED DESCRIPTION

[0059] Technical solutions for gated mesoporous nanomaterials based on dendrimers combined with aptamers such as Figure 1 As shown, the following steps are included:

[0060] (1) Loading signal molecules into mesoporous nanoparticles to obtain signal molecule-loaded mesoporous nanoparticles OSM@MSNs.

[0061] (2) coupling the target-specific aptamer to the OSM@MSNs obtained in step (1) to obtain the OSM@MSNs-aptamer coupled to the surface of the mesoporous nanoparticles carrying the signal molecule,

[0062] (3) coupling ssDNA with the nth generation carboxyl polyamide-amine dendrimer to obtain ssDNA-Gn, wherein n≥3.5,

[0063] The ssDNA is used to bind to the aptamer in step (2) and is competitively dissociated in the presence of the detection target.

[0064] (4) Assembling the ssDNA-Gn obtained in step (3) with the OSM@MSNs-aptamer obtained in step (2), and allowing the nth generation carboxyl polyamide-amine dendrimer to seal the mesoporous nanoparticles through the binding between the ssDNA and the aptamer.

[0065] The signal molecule may be one of rhodamine B, fluorescein isothiocyanate, Cy3, Cy5 and fluorescein. In the present invention, rhodamine B is selected as the signal molecule as an example.

[0066] The mesoporous nanoparticles can be mesoporous silica nanoparticles, mesoporous titanium dioxide nanoparticles, metal organic frameworks, mesoporous alumina, mesoporous magnetic beads, mesoporous ferrosoferric oxide or mesoporous copper sulfide nanoparticles. In the present invention, mesoporous silica nanoparticles are selected as mesoporous nanoparticles as an example.

[0067] Specifically, in step (2), when the target-specific aptamer is coupled to the OSM@MSNs obtained in step (1), the N=C=O group is introduced by functionalizing the surface of the OSM@MSNs obtained in step (1), and the end group of the aptamer is modified with an amino group, and the coupling is carried out by reaction between the N=C=O group and the amino group;

[0068] Alternatively, the surface of OSM@MSNs obtained in step (1) is functionalized to introduce amino groups, the terminal group of the aptamer is modified with -SH groups, and the aptamer is coupled with N-α-maleimidoacetyl-oxysuccinimide ester.

[0069] Alternatively, -SH groups are introduced by functionalizing the surface of OSM@MSNs obtained in step (1), and the end groups of the aptamer are modified with amino groups, and the aptamer is coupled with N-α-maleimidoacetyl-oxysuccinimide ester;

[0070] Alternatively, the surface of OSM@MSNs obtained in step (1) is functionalized to introduce amino groups, the end group of the aptamer is modified with amino groups, and the aptamer with amino groups is coupled with glutaraldehyde or (bis(sulfosuccinimidyl) suberate);

[0071] In step (3), when ssDNA is coupled with the nth generation carboxyl polyamide-amine dendrimer to obtain ssDNA-Gn, the two undergo a coupling reaction mediated by EDC / NHS.

[0072] The mesoporous nanoparticles have a mesopore size of 3 to 5 nm.

[0073] The technical solution of the present invention is described below with reference to specific embodiments.

[0074] Example 1

[0075] A method for preparing a gated mesoporous nanomaterial based on dendrimers combined with aptamers comprises the following steps:

[0076] (1) Rhodamine B loaded into silica mesoporous nanoparticles (RhB@MSNs)

[0077] 100 mg of silica mesoporous nanoparticles (MSNs, Sigma, catalog number: 748161) (particle size: 200 nm, pore size: 4 nm) were mixed with 76.64 mg of rhodamine B. Then 10 mL of acetonitrile was added to the mixture and allowed to react for 24 h to fully load rhodamine B into the mesoporous material.

[0078] (2) Functionalization of the microsphere surface, introduction of N=C=O groups

[0079] 247.6 μL of isocyanatepropyltriethoxysilane was added to the reaction solution in step (1) and the mixture was shaken at room temperature for 5.5 h. Then, the mesoporous particles were filtered with filter paper and washed once with 5 mL of acetonitrile. Finally, the particles were dried at 38°C for 18 h before use.

[0080] (3) Surface coupling of mesoporous nanoparticles loaded with rhodamine B with aptamers (i.e., RhB@MSNs-aptamers)

[0081] First, prepare a 1mM Rhodamine B acetonitrile solution; then take 1mg of the nanoparticles in step (2) and 700μL of the prepared Rhodamine B acetonitrile solution, 2μL of triethylamine and mix them evenly, then add 100μL of the aptamer solution with amino-modified end groups (its initial concentration is 10μM). After the mixed solution is shaken for 3h, centrifuged at 3min×3000g, the precipitate is taken, and then replaced and washed twice with Tris-HCL buffer (pH=7.5), and freeze-dried. The aptamer sequence used in this experiment is It is an ochratoxin A-specific aptamer.

[0082] (4) Preparation of the 3.5th generation carboxyl polyamide-amine dendrimer (i.e., G3.5-COOH) and ssDNA conjugate (i.e., ssDNA-G3.5)

[0083] The ssDNA containing 1 μM amino-modified DNA (i.e., NH 2 -ssDNA, wherein ssDNA can be complementary to the aptamer base pairing), 1nM G3.5-COOH, 5mM N-hydroxysulfosuccinimide (NHS) and 2mM 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC) reaction mixture was reacted in 0.1M 2-morpholineethanesulfonic acid (MES) solution (pH 6.0) at room temperature for 2 hours. Subsequently, the resulting mixture was filtered with an Amicon Ultra centrifugal filter (cutoff value of 10KDa), and the ssDNA-G3.5 conjugate (Mw>10KDa) was collected and dissolved in 0.1mL Tris-HCL buffer (pH=7.5) to obtain a mixed solution for standby use.

[0084] (5) ssDNA-G3.5 is coupled to MSNs-aptamer to seal MSNs

[0085] 1 mg of the MSNs-aptamer nanoparticles obtained in step (3) was mixed with 0.1 mL of the mixed solution obtained in step (4), reacted at room temperature for 30 min, then centrifuged at 3000 g for 3 min, and the precipitate was collected. Finally, 0.1 mL of Tris-HCL buffer (pH = 7.5) was added to obtain a gated mesoporous nanomaterial of dendrimer-bound aptamers, wherein the signal molecule was rhodamine B (i.e., RhB@MSNs-aptamer / G3.5). The ssDNA sequence used in the experiment was

[0086] (6) Sample pad preparation

[0087] The sample pad material is glass fiber, which is pre-soaked in blocking buffer for 12 hours and then dried for use. The blocking buffer composition is 1X PBS (pH 7.4), 5% bovine serum albumin, 5% sucrose, 0.01% Tween-20, 0.02% Triton X-100, and 0.01% proclin 300.

[0088] (7) Bonding pad production

[0089] The main material of the conjugate pad is a polyester membrane, which is pre-soaked in a blocking buffer for 12 hours, dried, and then sprayed with 1 mg / mL of RhB@MSNs-aptamer / G3.5 prepared in step (5) and 10 μg / mL of fluorescein, and then dried for use. The blocking buffer composition is 1X PBS (pH 7.4), 5% bovine serum albumin, 5% sucrose, 0.01% Tween-20, 0.02% Triton X-100, and 0.01% proclin 300.

[0090] (3) T-line and C-line

[0091] 1 mg / mL anti-rhodamine B and anti-fluorescein antibodies were sprayed on the T and C lines of the nitrocellulose membrane, respectively, with a spacing of 4 mm between the T and C lines, and then dried at 37°C.

[0092] (4) Assembly

[0093] The test strips consist of a sample pad, conjugate pad, nitrocellulose membrane and adsorbent pad overlap assembly assembled on a PVC card. First, the conjugate pad is slightly covered on the nitrocellulose membrane, and then the sample pad is placed to overlap the conjugate pad. The conjugate pad and sample pad are placed at the end of the nitrocellulose membrane, and on the other side of the membrane, the adsorbent pad overlaps the nitrocellulose membrane. All overlap areas are 2mm in length. The final assembled card is cut into 3mm long strips and then stored in a desiccator before use.

[0094] The schematic diagram of the prepared test strip structure and the schematic diagram of the detection principle are as follows Figure 2 shown.

[0095] Example 2 Characterization

[0096] 1. Aptamer characterization: Coupling of aptamers and mesoporous nanomaterials

[0097] By using a fluorescently labeled aptamer, coupled to the surface of the mesoporous nanoparticle according to step (3) in Example 1, the success of coupling the aptamer to the surface of the mesoporous nanoparticle is characterized. Figure 3 As shown in the figure, the number of aptamers on the surface of the aptamer chemical coupling group is significantly higher than that of the aptamer-free group and the aptamer physical adsorption group, which proves that the aptamer is successfully coupled to the surface of the mesoporous nanoparticles. The value of the aptamer chemical coupling group is 2338±861, indicating that 2338±861pmol of aptamer can be coupled per mg of mesoporous nanoparticle surface. The aptamer sequence used in this experiment is:

[0098] 2. Coupling of ssDNA and G3.5

[0099] Similarly, by step (4) using fluorescently labeled ssDNA (i.e. ) was coupled to G3.5 to characterize ssDNA-G3.5. Figure 4 As shown in the figure, the fluorescence intensity of G3.5+ssDNA (chemical coupling group) is significantly higher than that of G3.5 group and G3.5+ssDNA (physical adsorption group), which proves that ssDNA is successfully coupled to G3.5. Subsequently, the number of ssDNA coupled to the G3.5 surface was calculated by using the standard curve, and the results showed that one G3.5 molecule surface can couple 44±6 ssDNA (3 repeated experiments).

[0100] 3. Particle size

[0101] In addition, by comparing the particle size of the synthesized particles, the success of the synthesis in steps (1) to (5) was confirmed again. Figure 5 As shown in the figure, the original G3.5 molecular size is about 4.1nm. After coupling with ssDNA, its size increases to 9.9nm, indicating that its coupling is successful. In addition, the original MSNs particle size is 205.3nm. When it is coupled with the aptamer (i.e., MSNs-aptamer), its particle size increases to 255.8nm, proving that its coupling is successful. Subsequently, after the MSNs-aptamer is coupled with ssDNA-G3.5 again, its particle size increases again to 291.5nm, indicating that the synthesis of MSNs-aptamer / G3.5 is successful.

[0102] Example 3 Gating Performance Test

[0103] The gating performance and the release rate of the signal molecule were verified by adding ochratoxin A to stimulate the gating of the material of the present invention (i.e., RhB@MSNs-aptamer / G3.5) and releasing the signal molecule Rhodamine B. At the same time, the "blocking method" and the "bridging method" were used for comparison.

[0104] Among them, the plugging method: the plugging method structure is as follows Fig. 9 As shown, silica nanoparticles MCM-41 (pore size 3 nm, Sigma, catalog number 926876) were selected to introduce N=C=O groups on its surface through step 2 of Example 1, and then loaded with rhodamine B and coupled with a capping aptamer with an amino terminal group through step 3 to complete the preparation of silica nanoparticles by the "plugging method", and the sequence is:

[0105] Bridge method: The structure of bridge method is as follows Fig.10 As shown, silica nanoparticles MCM-41 (with a pore size of 3 nm, Sigma, item number 926876) were selected to introduce N=C=O groups on their surface through step 2 in Example 1. Then, it was loaded with rhodamine B and coupled with the single-stranded DNA of the arm with an amino terminal group through step 3. Subsequently, the product was base-paired with the sealing aptamer. Specifically: 100 μL of 10 μM sealing aptamer was added to 1 mg of the obtained product, reacted at room temperature for 30 minutes, then centrifuged for 3 min × 3000 g, the precipitate was taken, and finally 0.1 mL of Tris-HCL buffer (pH = 7.5) was added to obtain the silica nanoparticles made by the "bridge method". The single-stranded DNA of the arm is: The blocking aptamer sequence is:

[0106] like Figure 6 As shown in A, positive samples can open the gate of mesoporous nanoparticles sealed by three different methods and release signal molecules. However, in the present invention, the signal molecule release performance of RhB@MSNs-aptamer / G3.5 is better than that of the other two methods. Observations show that the signal molecules of the material of the present invention have reached the maximum value at 6 minutes, while the signal molecule release rate of the other two methods is still showing an upward trend at 30 minutes. The results prove that in the present invention, the gate can quickly respond to the target substance and quickly release the signal molecules, which can reach the maximum value within 6 minutes, meeting the application requirements on the test strip.

[0107] In addition, under negative sample testing ( Figure 6B), it can be seen that the signal molecules in the gated mesoporous material of the present invention are almost not released, and its value shows a stable trend, which proves that its sealing is stable and will not leak signal molecules. However, the signal molecules in the mesoporous materials of the other two sealing methods are continuously released, and their values ​​show a continuous upward trend, which proves that their sealing is unstable, signal molecules leak, and cannot meet the requirements of application on test strips.

[0108] In addition, in order to test the effect of milk matrix on the sealing stability of gated mesoporous materials, mesoporous nanoparticles sealed by three different methods were immersed in negative milk matrix, and the release of signal molecules was observed. Figure 7 As shown, the signal molecules of the gated mesoporous material of the present invention are almost not released, which proves the stability of its sealing. This is likely due to the antifouling function of G3.5, which makes its nanomaterial have good anti-nonspecific adsorption effect. The signals of the mesoporous particles sealed by the other two methods increase significantly and rapidly, proving that other substances in milk can open the gate and release signal molecules, so they are not suitable for use in rapid detection strips.

[0109] Example 4 Real sample detection

[0110] A rapid test strip based on gated mesoporous nanoparticles with dendrimers and aptamers was prepared by steps (6) to (9) and tested in real milk samples with different concentrations (50, 100, 200, 500 fg / mL and 1, 10, 100 ng / mL) of ochratoxin A. Figure 8 As shown in the figure, when ochratoxin A is at 50fg / mL and above, the T line is colored, proving that its visual detection limit is 50fg / mL, which is better than other forms of test strips reported in the prior art. In addition, when a negative sample is used to test it (see 0fg / mL), its T line does not show color, proving that the test strip has no false positives.

Claims

1. A method for preparing a gated mesoporous nanomaterial, wherein the gated mesoporous nanomaterial can be used to prepare a test strip, characterized in that: The following steps are involved: (1) Loading signal molecules into mesoporous nanoparticles to obtain signal molecule-loaded mesoporous nanoparticles, i.e., OSM@MSNs. (2) coupling the target-specific aptamer to the OSM@MSNs obtained in step (1) to obtain a mesoporous nanoparticle surface-coupled aptamer loaded with a signal molecule, i.e., an OSM@MSNs-aptamer. (3) coupling ssDNA with the nth generation carboxyl polyamide-amine dendrimer to obtain ssDNA-Gn, The ssDNA is used to bind to the aptamer in step (2) and is competitively dissociated in the presence of the detection target, wherein n≥3.5, (4) Assembling the ssDNA-Gn obtained in step (3) with the OSM@MSNs-aptamer obtained in step (2), and allowing the nth generation carboxyl polyamide-amine dendrimer to seal the mesoporous nanoparticles through the binding between the ssDNA and the aptamer.

2. The method for preparing gated mesoporous nanomaterials according to claim 1, characterized in that: The signal molecule is at least one of rhodamine B, fluorescein isothiocyanate, Cy3, Cy5 and fluorescein.

3. The method for preparing gated mesoporous nanomaterials according to claim 1, characterized in that: The mesoporous nanoparticles are mesoporous silicon dioxide nanoparticles, mesoporous titanium dioxide nanoparticles, metal organic frameworks, mesoporous aluminum oxide, mesoporous magnetic beads, mesoporous ferrosoferric oxide or mesoporous copper sulfide nanoparticles.

4. The method for preparing gated mesoporous nanomaterials according to claim 1, characterized in that: In step (2), when the target-specific aptamer is coupled to the OSM@MSNs obtained in step (1), the N=C=O group is introduced by functionalizing the surface of the OSM@MSNs obtained in step (1), and the end group of the aptamer is modified with an amino group, and the coupling is carried out by reaction between the N=C=O group and the amino group; Alternatively, the surface of OSM@MSNs obtained in step (1) is functionalized to introduce amino groups, the terminal group of the aptamer is modified with -SH groups, and the aptamer is coupled with Na-maleimidoacetyl-oxysuccinimide ester. Alternatively, -SH groups are introduced by functionalizing the surface of OSM@MSNs obtained in step (1), the end groups of the aptamer are modified with amino groups, and the aptamer is coupled with Na-maleimidoacetyl-oxysuccinimide ester; Alternatively, the surface of OSM@MSNs obtained in step (1) is functionalized to introduce amino groups, the end group of the aptamer is modified with amino groups, and the aptamer with amino groups is coupled with glutaraldehyde or (bis(sulfosuccinimidyl) suberate); In step (3), when ssDNA is coupled with the n-generation carboxyl polyamide-amine dendrimer to obtain ssDNA-G3.5, the two are coupled by EDC / NHS-mediated reaction.

5. The method for preparing gated mesoporous nanomaterials according to claim 1, characterized in that: The mesoporous nanoparticles have a mesopore size of 3 to 5 nm.

6. The gated mesoporous nanomaterial prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the gated mesoporous nanomaterial according to claim 6 in preparing a detection kit, wherein the kit comprises a detection test strip, the detection test strip comprises a conjugate pad, a detection line T line, and a quality control line C line, and the gated mesoporous nanomaterial is embedded in the conjugate pad.

8. A detection kit, comprising a test strip, wherein the test strip comprises a conjugate pad, a detection line T line, and a quality control line C line, characterized in that: The conjugate pad is embedded with the gated mesoporous nanomaterial according to claim 6.

9. The detection kit according to claim 8, characterized in that: The conjugate pad is also embedded with fluorescein, the detection line T is embedded with an antibody against the signal molecule, and the quality control line C is embedded with an anti-fluorescein antibody against the fluorescein.

Citation Information

Patent Citations

  • Nucleic acid aptamer fluorescence test strip, method for preparing same and application of nucleic acid aptamer fluorescence test strip

    CN107796938A

  • Multifunctional specific DNA hybridization-gated mesoporous silica gene carrier and preparation method and application thereof

    CN110106204A

  • Preparation method and application of PH reversible controlled release meso-porous silicon nanometer drug delivery system

    CN111789823A

  • Staphylococcus aureus detection method based on aptamer gated mesoporous silica

    CN113640274A

  • Novel coronavirus specific binding complex and carrier

    CN115433732A